PRESERVASI PENGETAHUAN UPACARA TRADISI TINGKEBAN MASYARAKAT JAWA TRANSMIGRASI DI SITIUNG 2 KABUPATEN DHARMASRAYA SUMATERA BARAT - Shinta Aprilya Ningrum; Desriyeni Desriyeni (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2023)
This study aims to describe the meaning of traditional ceremonies tingkeban, tools and materials used in the tingkeban traditional ceremony, tingkeban traditional ceremonial procession; and ceremonial knowledge preservation activities the tingkeban tradition of the Javanese transmigration community in Sitiung 2 District Dharmasraya, West Sumatra. This research is a type of descriptive qualitative research with a case study approach. Data collection techniques using observation, interviews, and documentation studies. Data validation technique using triangulation, namely data source triangulation, theory triangulation, and method triangulation.The data validation technique uses the Miles and Hubermen models consisting of data reduction, data presentation, drawing conclusions and verification. The results of this research are as follows. First, the traditional ceremony tingkeban Jawa transmigration has a very important meaning in life, namely as a means of praying so that the baby and mother are healthy and safe, as a rejection of reinforcements, a gathering place for neighbors, relatives and friends surrounding communities, strengthen brotherhood, and preserve traditional ceremonies brought by the ancestors. Third, the series of processions that are carried out are sacred rituals and full of meaning. Fourth, knowledge preservation activities carried out namely socialization and externalization. Socialization activities are carried out with face-to-face direct delivery, imitation, and delivery through the medium of wayang. Outreach activities become easier because the community already has awareness to carry out traditional ceremonies tingkeban. In addition, externalization activities in the preservation of ceremonial knowledge the tingkeban tradition is carried out by documenting it in the form of books, videos, articles and journals. In externalization activities, the community is still minimal accessing information and knowledge from tingkeban traditional ceremony documents.